Experimental Research for the Single-Stage and Double-Stage Two-Bladed Savonius Micro-Sized Turbine for Rain Water Harvesting (RWH) System (International Journal of Innovative Research in Computer Science & Technology, 2020)
The performance of the single-stage and  double-stage two-bladed micro-sized turbines for the  Rain Water Harvesting (RWH) System is investigated in  this article. The RWH system is a technique of collecting  rainwater and storing it in a tank before reusing it for a  specific purpose. The emphasis of this paper's  performance analysis was on the electrical generating  capacity of the Savonius turbine. The Savonius turbines  were developed and constructed out of an aluminum sheet  with an aspect ratio of 1.8, a height of 8 cm, and a  diameter of 4.5 cm. When incoming water travels from  the water tank via the micro-Savonius blades in the  pipeline, the performance of single-stage and double stage designs is evaluated in terms of electrical power  production. According to the findings, the planned and  constructed systems work well in terms of maintaining a  constant voltage and current. The single-stage rotor  outperformed the two-stage rotor, which can create  almost twice the power. When a single-stage two-bladed  Savonius rotor is utilized instead of a double-stage rotor,  the rotor may spin at up to 1280 rpm. The two-bladed  Savonius micro-turbine has a single stage and can light  0.3 watt LED lights.
Keywords: Savonius Turbine; Rain Water Harvesting; Blade Rotor; Micro-Sized; Single-Stage; Double-Stage